Collaborative Governance Process by Disaster Resilient Villages (DESTANA) to Improve Performance - Agus Widiyarta; Arimurti Kriswibowo (PT FORMOSA CENDEKIA GLOBAL, 2023)
The existence of a Disaster Resilient Village (Destana) is very important for the region in mitigating flood disasters. Destana has the function of protecting the community, increasing community participation, increasing capacity, increasing government capacity in providing resource and technical support for disaster risk reduction, and increasing cooperation between stakeholders. This function will be achieved well if there is collaboration with other stakeholders. Destana's performance will be better if it can create collaborative governance through the right process. The process begins with face-to-face, namely conducting dialogue on existing problems with stakeholders. Followed by a trust-building process, namely creating a sense of trust because of shared interests, after that, the commitment to the process is a joint agreement to carry out the program. The next process is sharing understanding, which is raising awareness together to overcome floods followed by the Intermediate outcomes process, which is evaluating the temporary results of the collaborative process. These steps will be able to run optimally to improve Destana's performance if the right organization is selected to collaborate with so that a scheme is needed that fits the conditions of each village.